2022
DOI: 10.1155/2022/4623869
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mental Health First Aid Training Courses on Patients’ Mental Health

Abstract: Background. With the prevalence of mental issues worldwide, more and more people are suffering from psychological torture. Mental Health Gap Action Program (mhGAP) has been introduced to improve the life quality of humans. Objectives. To explore and synthesize evidence of participants’ experience of mental health first aid (MHFA) training course. Method. Peer-reviewed qualitative evidence was systematically reviewed and thematically synthesized. Cumulative Index to Nursing and Allied Health Literature (CINAHL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…When individuals perceive mental illness as a sign of weakness, it profoundly decreases the likelihood of sharing feelings and seeking treatment. A systematic review showed a reduction in stigma and avoidance after taking the MHFA course (Zeng et al, 2022). Positive changes in stigma were also observed among church participants, t[26] = -2.948, p < .01, with the post-mean score for stigma (M = 16.48, SD = 2.47) higher than that of the pretest (M = 14.04, SD = 3.54) (Costello et al, 2020).…”
Section: Reduced Stigma About Mental Health Problemsmentioning
confidence: 99%
“…When individuals perceive mental illness as a sign of weakness, it profoundly decreases the likelihood of sharing feelings and seeking treatment. A systematic review showed a reduction in stigma and avoidance after taking the MHFA course (Zeng et al, 2022). Positive changes in stigma were also observed among church participants, t[26] = -2.948, p < .01, with the post-mean score for stigma (M = 16.48, SD = 2.47) higher than that of the pretest (M = 14.04, SD = 3.54) (Costello et al, 2020).…”
Section: Reduced Stigma About Mental Health Problemsmentioning
confidence: 99%